Promocja miasta, państwa i idei – „zielona” ceremonia otwarcia IO Rio 2016 w przekazach medialnych na świecie - Sajna, Radosław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Olympic Games are not only global sport events, but also a great opportunity to brand cities and countries that host sportsmen and sportswomen from around the world, and to promote ideas. The opening ceremony of the Rio Olympics 2016 was full of “green” (ecological) messages and symbols, beside of presented cultural, historical and environmental values of Brazil. In this article some effects of a content analysis of media (opinion newspapers on-line) from 30 countries from different continents were presented to answer the question: how the global media coverage could serve to promote Rio de Janeiro, Brazil and the idea of the sustainable development.